Curriculum Renewal for Interprofessional Education in Health : Final Report. - Dunston, Roger; Forman, Dawn; Rogers, Gary; Thistlethwaite, Jill; Yassine, Tagrid; Hager, Jane; Manidis, Marie; Rossiter, Chris (Office for Learning and Teaching, 2014)
This is the final report from a project that responds to the urgent need for curriculum renewal in health education - in particular, the need to graduate students from all health professions with well-developed interprofessional practice (IPP) capabilities. IPP capabilities are identified as essential for delivering health services that are safer, more effective, and more sustainable. Significant interprofessional education (IPE) initiatives have occurred internationally. However, within the Australian higher education context, IPE remains relatively undeveloped, and is not well integrated with core elements of the curriculum. In addressing this national challenge, the project contributes in two areas. Firstly, it produced and disseminated a range of IPE curriculum resources: a curriculum framework, generic capability statements, learning outcomes and assessment methods. Secondly, it produced and disseminated resources to guide and support curriculum change.